2022
DOI: 10.1111/andr.13192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet and antihyperglycemic drugs on erectile dysfunction: A systematic review

Abstract: Background: Erectile dysfunction is recognized as one of the complications of diabetes mellitus. To date, a wide gap of knowledge is present on the efficacy of pharmacological treatments of diabetes mellitus on erectile function, acting not only through metabolic control. Similarly, the effects of different diet regimens on erectile dysfunction are still debated. Objectives:We aimed to explore the effects of diet and antihyperglycemic drugs, considering both old and novel therapeutic approaches, on erectile fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 144 publications
1
14
0
Order By: Relevance
“…The diet followed by the patients was almost on the basis of the Mediterranean diet, when followed. As known, the Mediterranean diet may be associated with an improvement of EF [ 14 , 21 , 40 ]. The role of diet, when associated with antidiabetic drugs, allows to explain the favorable trend, though not significant, on the IIEF-5 score, compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diet followed by the patients was almost on the basis of the Mediterranean diet, when followed. As known, the Mediterranean diet may be associated with an improvement of EF [ 14 , 21 , 40 ]. The role of diet, when associated with antidiabetic drugs, allows to explain the favorable trend, though not significant, on the IIEF-5 score, compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the effect of antidiabetic treatment on erectile function (EF), a limited number of studies focused on humans are available [ 12 , 13 , 14 ], so the data are still limited on ED. A study conducted on Metformin use in diabetic men with ED showed an increased International Index of Erectile Function (IIEF) score after treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, two sensitivity analyses were additionally performed to assess the robustness of our findings. In the first sensitivity analysis, we excluded participants taking medicines that potentially affect erectile function, including antidepressants (42), antipsychotics (43), antihyperglycemic agents (9,44), sex hormones and corticosteroids (45). In the second sensitivity analysis, a stricter criterion of ED was used.…”
Section: Discussionmentioning
confidence: 99%
“…Diet is a potential source of chronic low-grade inflammation which is related to the pathogenesis of ED (8). Previously, some dietary patterns, especially anti-inflammatory diet, have been linked to ED (9,10). For example, Mediterranean diet is a kind of anti-inflammatory diet, and recently a long-term randomized clinical trial by Maiorino et al has noticed a protective effect of Mediterranean diet on erectile function, as well as a reduction of C-reactive protein levels in males with newly diagnosed type 2 diabetes (T2DM) (11).…”
Section: Introductionmentioning
confidence: 99%